The Cobra Effect in TVET Policy Making: A Macro-Micro-Macro-Level Analysis of Exemplary Cases From Germany - Johannes Karl Schmees; Janika Grunau (International Journal for Research in Vocational Education and Training)
Context: Unlike education policy for general education, technical and vocational education and training (TVET) policy often focuses on societal needs, ignoring the attitudes and subsequent behaviors of learners. As a result, the impact of TVET policies is not what was expected and sometimes even counterproductive. Starting from this, we use macro-micro-macro-level analysis inspired by Coleman's boat theorem to reflect on three exemplary cases of German TVET policy. These TVET policies have in common that they aim to reduce skills shortages in certain occupations.